Assessing Intercultural Competence In English Language Learners: Perspectives On Local Cultural Integration In Indonesia - -, Andi Asrifan; Anita Candra Dewi (STIT Buntet Pesantren Cirebon, 2024)
This research examines Indonesian university students' intercultural competence (ICC) development and assessment in English language courses, highlighting the importance of cultural integration and interaction. A detailed case study, the study examines students' encounters with foreign cultures using interviews, focus group discussions, and academic performance analysis against Indonesia's rich cultural diversity and historical context. Local community involvement promotes cultural learning, and Indonesia must continue to improve ICC in EFL teaching. The study also confirms the ICCit instrument's ability to measure intercultural competence's behavioral involvement. This research illuminates the intricacies and context-dependence of intercultural competence and the benefits of cultural integration and understanding for society, which can be used to improve ICC in language education.